Estudo comparativo entre paraju e madeira plástica para aplicação na construção civil - Mastela, Leonor da Cunha; Breda, Augusto Melo Moulin; Segundinho, Pedro Gutemberg de Alcântara; Andrade, Wendel Sandro de Paula; Boa, Ana Carolina; Marcchiori, Thaís de Souza; Gonçalves, Fabricio Gomes; Paes, Juarez Benigno (Ambiente Construído, 2025)
In the search for products which meet to human needs and collaborate with the environment, comes up the wood-plastic composite as a good alternative. It is a material which comes from wood and plastic residues, has considerable environmental appeal and had higher resistance to moisture than wood. This work aimed to evaluate a wood-plastic composite in comparison to natural paraju wood (Manilkara sp.) in using these materials for civil construction. Physical, mechanical and biodeterioration properties were tested. Despite not presenting mechanical strengths similar or superior to paraju wood, the composite had satisfactory and better values for density, shrinkage and swelling, as well as resistance to the termite Nasutitermes corniger. Elements produced from plastic require greater care in relation to the propagation of flames. The wood-plastic composite cannot be used as a structural element. However, it can be used in civil construction as cladding on facades, floors, and room dividers.